Algunas cruces procesionales del siglo XVII en el antiguo obispado de León - Alonso Benito, Javier (Estudios humanísticos. Geografía, historia y arte, 1997)
The seventeenth century constitutes a period in history of the Spanish silversmithing wiht very distinctive characteristics. This is reflected in a noteworthy fashion in the working of processional crosses, such are preservad in the ancient bishopric of León, as this study attempts to relate. However, despite the stereotyping of models, there is also some evolution no forms and decoration as the century progresses. The examples to be considered illustrate this.